Konsep Pendidikan Jiwa Menurut Ibnu Qayyim: Pendekatan Spiritualitas dan Akhlak dalam Islam - Azhar, Dzul; Bahij, Muhammad Alfan; Hasan, Ismail; Rohimah, Siti (Lembaga Yasin AlSys, 2024)
This paper examines the concept of spiritual education according to Ibn Qayyim Al-Jawziyya, who identifies two main types of trials: fitnah syubhat (caused by weak understanding and lack of knowledge) and fitnah syahwat (caused by a corrupt heart and pursuit of desires). Ibn Qayyim emphasizes the importance of having a tranquil soul (an-nafs al-muthma'innah) that fosters commendable qualities and noble character. Additionally, the concept of tahqiq ‘ubudiyah is described as the process of internalizing the values of worship in daily life as a form of devotion to Allah. This spiritual education also includes muhasabah, or self-examination, to consistently evaluate and improve oneself. Dzikrullah, or remembering Allah, is deemed essential as it provides peace of heart, erases sins, and brings great rewards. By integrating the values of worship and self-examination, Ibn Qayyim's spiritual education aims to develop a strong and Islamic character, enhancing faith through patience, reliance on Allah (tawakkul), and constant remembrance (dhikr). This spiritual education helps individuals overcome worldly temptations, improve their spiritual quality, and guide them toward a meaningful and Allah-pleasing life.